Metode Perkembangan Agama dan Moral bagi Anak Usia Dini di TK Witri 1 Kota Bengkulu - Jumi Alia Tini; Tri Adi Ningsih; Yolanda Maisah Dora; Vira Feriza (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2025)
This study examines methods of religious and moral development for early childhood at Witri 1 Kindergarten in Bengkulu City. The main objective of this study is to understand how teachers instill religious and moral values through learning activities that are integrated with children's daily lives. This study uses a qualitative descriptive approach with observation, interview, and documentation techniques. The results show that religious values are developed through the habit of praying, greeting others, and simple worship practices appropriate to the children's stage of development. Meanwhile, moral values are developed through the habit of polite behavior, honesty, cooperation, and responsibility in learning and playing activities. Teachers act as role models by setting positive examples and utilizing storytelling, singing, and educational games to reinforce children's understanding. The study concludes that habituation, role modeling, and contextual activities are effective strategies in shaping the religious and moral development of early childhood. The conducive learning environment at TKWitri 1 supports the development of religious and moral character in children from an early age.